Goats: Challenges for increased productivity and improved livelihoods - Devendra, C. (1999)
In animal production systems, the value of a species increases in relation to its adaptation, capacity to make socioeconomic contributions, capacity to fill market opportunities, and potential for increasing productivity. In the case of goats, their role and potential contribution to increased productivity are impeded by controversy about their destructive habits, poor understanding of their attributes, functional values, and links to the poverty focus, which together have not helped their contribution to improving natural resource management. Research and development efforts that can significantly improve productivity from goats can simultaneously enhance the livelihoods of the poor. Resource allocation by national programmes and donor agencies to research and development projects on these animals is generally poor. In the search for efficiency in the improved use of the available animal genetic resources, more enlightened thinking is necessary about the role that goats could play. This must be backed by more resources and the use of interdisciplinary systems in priority agroecological zones to increase their productivity, and by so doing, this will enhance the livelihoods of the poor, and protect the environment. Topics discussed in this paper include population size and distribution; interactions with the environment; poverty; gender; goat production systems; contribution to human nutrition; economic contribution; post production systems; and opportunities for research and development.